2021
DOI: 10.1103/physrevb.103.214415
|View full text |Cite
|
Sign up to set email alerts
|

Local origin of the strong field-space anisotropy in the magnetic phase diagrams of Ce1xLaxB6 measured in a rotating magnetic field

Abstract: Cubic f-electron compounds commonly exhibit highly anisotropic magnetic phase diagrams consisting of multiple long-range-ordered phases. Field-driven metamagnetic transitions between them may depend not only on the magnitude, but also on the direction of the applied magnetic field. Examples of such behavior are plentiful among rare-earth borides, such as RB 6 or RB 12 (R = rare earth). In this work, for example, we use torque magnetometry to measure anisotropic field-angular phase diagrams of La-doped cerium h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 91 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…However, among all 4f elements, the Ce 3+ ion is perhaps the only lanthanide where DFT models are capable of producing some single-particle properties reliably, in particular spin densities. In our previous studies of both metallic and insulating Ce-based systems like CeB 6 [14] and KCeS 2 [54], we have shown that the accuracy of DFT in predicting the spin density distribution within the DFT/PBE/PAW framework compared to CASSCF-level calculations is surprisingly high.…”
Section: A Density Functional Theory (Dft) Calculationsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, among all 4f elements, the Ce 3+ ion is perhaps the only lanthanide where DFT models are capable of producing some single-particle properties reliably, in particular spin densities. In our previous studies of both metallic and insulating Ce-based systems like CeB 6 [14] and KCeS 2 [54], we have shown that the accuracy of DFT in predicting the spin density distribution within the DFT/PBE/PAW framework compared to CASSCF-level calculations is surprisingly high.…”
Section: A Density Functional Theory (Dft) Calculationsmentioning
confidence: 96%
“…Torque magnetometry measurements in magnetic fields up to 18 T were carried out on a 5.0 mg single crystal of Ce 3 Pd 20 Si 6 at the National High Magnetic Field Laboratory using the setup described in Ref. 14. The sample, oriented with an x-ray Laue camera, was cut in two halves, the approximately equal pieces were glued to two cantilever paddles made of beryllium copper and mounted on a cylindrical sample holder placed inside the rotator with its rotation axis parallel to the (110) and (001) crystal axes, respectively.…”
Section: Field-angle Phase Diagrammentioning
confidence: 99%
See 3 more Smart Citations